THE STUDY OF MOSFETS PARALLELISM AND EFFECTS ON SRBC CIRCUIT - MAKHTAR, NUR AMIZA (Universiti Teknologi Petronas, 2011)
Tiris project is about the study of MOSFETs parallelism and its effects on SRBC circuit. Output current in the circuit will always be the main concern. Other main issue is high conduction loss. Hence, MOSFETs parallelism is used to produce high output current and reduce body diode conduction loss. The applied circuit is Synchronous Rectifier Buck Converter (SRBC). There are several configurations in paralleling the MOSFETs at both switches from I x 1 up to 4x4. The simulation work will be conducted into two modes which are in Continuous Conduction Mode (CCM) and Discontinuous Conduction Mode (DCM). Analysis will be carried out in order to choose the optimized configuration that gives the best outcome based on design requirement such as produce high output current, minimal body diode conduction loss and 3V as output voltage. It is found that for CCM, the optimized configuration is (SJ:4, S2:1). As for DCM, the optimized configuration is (SJ:4, S2:3). Once the optimized configuration has been chosed, it will then compare to other SRBC circuits. They are SRBC with Conventional Gate Driver (CGD), Adaptive Gate Driver (AGD), compensator and AGD, and lastly SRBC with MPPT controller. For CCM, it is found that among all, MOSFETs parallelism can produce the second higher output current by 863.84 rnA as SRBC with MPPT controller produces the highest output. Whilst for DCM, MOSFETs parallelism also produce second higher output current and successfully eliminate body diode conduction loss. Further details will be discussed in this report.